2007
DOI: 10.1897/05-629r.1
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural intensity and landscape structure: Influences on the macroinvertebrate assemblages of small streams in northern Germany

Abstract: The present study aimed to relate aquatic macroinvertebrate community composition to agricultural intensity and landscape structure. A total of 360 streams were investigated within the Aller river basin in northern Germany. The study area is typical of central German arable agricultural regions, but the small streams were of low dilution potential. These streams were characterized for abiotic parameters (including modeled potential for diffuse inputs from agricultural sources) and macroinvertebrate communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 32 publications
1
53
0
1
Order By: Relevance
“…anthropogenic stressors (Schäfer et al, 2007(Schäfer et al, , 2011a. Furthermore, Schriever et al (2007b) found 60 that SPEAR pesticides was the biological parameter best describing stream macroinvertebrate 61 community responses to a modelled indicator of pesticide surface runoff (RP). In contrast, 62 Rasmussen et al (2011) were unable to link RP with SPEAR pesticides using a large dataset of small 63 Danish streams, which could be due to the presence of wider buffer strips along Danish streams 64 compared to German streams.…”
Section: Introduction 32mentioning
confidence: 99%
“…anthropogenic stressors (Schäfer et al, 2007(Schäfer et al, , 2011a. Furthermore, Schriever et al (2007b) found 60 that SPEAR pesticides was the biological parameter best describing stream macroinvertebrate 61 community responses to a modelled indicator of pesticide surface runoff (RP). In contrast, 62 Rasmussen et al (2011) were unable to link RP with SPEAR pesticides using a large dataset of small 63 Danish streams, which could be due to the presence of wider buffer strips along Danish streams 64 compared to German streams.…”
Section: Introduction 32mentioning
confidence: 99%
“…The current experimental ditch study (see also López-Mancisidor et al [23] and Brock et al [26]), a few field observations in streams (e.g., [15,[44][45][46]) and a simulation study using a metapopulation model [18] suggest that the ecological impact on insects and crustaceans may be smaller in exposed sections of water courses if only part of the system suffers insecticide stress. However, an important question at stake is: ''At the landscape level, how large should be the surface area of, and distance to, uncontaminated refuges to allow an overall acceptable impact (including recovery and effects at a distance) of pesticide-stress on populations and communities?'…”
Section: Consequences For Risk Assessmentmentioning
confidence: 79%
“…The RP of a site was based on the log 10 -transformed load (g) of a generic compound that could enter the water body along a 1,500-m stretch upstream. Runoff potential was correlated with other indicators of agriculture intensity, but the major effect of RP on macroinvertebrates in the Aller Catchment is from pesticide runoff and not from other causes [17]. We split the data set into five RP categories: very low, defined as RP > À10 but 4 (n ¼ 40 samples); low, > À4 but 3 (60); moderate, > À3 but 2 (100); high, > À2 but 1 (120); and very high, > À1 but 0 (40).…”
Section: Data Setsmentioning
confidence: 94%
“…We used a macroinvertebrate data set [17] We related change in species occurrence to an index of runoff potential (RP) [17]. The RP of a site was based on the log 10 -transformed load (g) of a generic compound that could enter the water body along a 1,500-m stretch upstream.…”
Section: Data Setsmentioning
confidence: 99%